Distribuição espacial da tuberculose drogarresistente no estado do Paraná - Silva, Leila Wiedmann Florentino da (2022)
Tuberculosis (TB) is a contagious and very old disease, which is currently a priority issue the world agenda, and among the leading causes of death in the world. Brazil is among the 30 countries with the highest amount of TB and TB-HIV, which are considered priorities for the control of the disease in the world. Although the World Health Organization as a country with a high amount of drug-resistant TB (TBDR) does not classify Brazil, the data should be carefully analysed. A major problem is that undiagnosed people with TBDR represent an additional risk for the transmission of the disease, because they transmit resistant bacilli. The objective of this study was to analyse the epidemiological situation and incidence of TBDR in the municipalities of Paraná State, according to geographical distribution. This is a retrospective epidemiological study, of ecological approach, with geographical analysis of the cases of TBDR resident in Paraná in the years 2013 to 2020, notified in the SITE-TB system. In the descriptive analysis, the data was presented in absolute and relative frequency. The gross rate for incidence was calculated by Microsoft Excel® 2016 software, and subsequently put together with the result of the shapefile of the state of Paraná by QGIS®. Spatial dependence was tested for municipal TBDR incidence rates, by means of the Moran's Global Index (Moran's I), and subsequently by spatial cluster analysis using the Getis-Ord Gi* statistic. Both tests were performed by GeoDa. In the studied period, out of 22,275 TB cases, 515 (2.5%) were TB cases reported as TBDR. The majority were male (n=395; 76.70%), white race (n=307; 59.61%), with 4 to 7 years of education (n=224; 43.50%). Primary resistance appeared in 73.59% (n=379) of the cases, and acquired or secondary resistance in 25.44% (n=131) of them, distributed in all regions of the state. The initial resistance pattern was monoresistance (n=336; 65.24%), followed by Rifampicin resistance (n=93; 18.06%); finally, the cured were 53.59% (n=276) of the total cases. As for relative risk (RR), the purely geographical analysis identified 8 risk clusters, the lowest with RR of 2.45 (95% CI 1.81 - 3.30) and the highest with RR 26.26 (95% CI 15.77 - 44.04). The spatio-temporal analysis identified 4 clusters, one of them between 2013 and 2016 - RR 9.89 (95%CI 6.39 -13.86).The remaining spatio-temporal risk clusters were identified in the period of 2017 to 2020, with the lowest RR being 3.99 (95%CI 3.41-5.61) and the highest RR being 5.60 (95%CI 3.22 - 9.30). We observed that TBDR is present in all regions of the state, concentratedin the eastern and northern counties, as well as high rate clusters for TBDR. The study showed an annual growth of TBDR cases - its vast majority with primary drug resistance. The spatial distribution of incidence and high-rate clusters provided an insight into the situation of TBDR in the state of Paraná, which allows specific strategies to be implemented and intensified by health managers in order to improve the actions of the TB control program to interrupt the chain of transmission of the resistant bacillus.